Current and promising therapeutic options for Dravet syndrome. (13th October 2022) - Riva, Antonella; D'Onofrio, Gianluca; Amadori, Elisabetta; Tripodi, Domenico; Balagura, Ganna; Iurilli, Valentina; Vari, Maria Stella; Verrotti, Alberto; Striano, Pasquale
ABSTRACT: Introduction: Dravet Syndrome (DS) is a developmental and epileptic encephalopathy carrying high-level psychobehavioral burdens. Although the disease has been known for almost 4 decades, and despite significant progress in the understanding of its physiopathology and natural course, the pharmacological treatment leaves patients and caregivers with significant unmet needs. This review provides a summary of the current and promising therapeutic options for DS Areas covered: PubMed and ClinicalTrials.gov were screened using 'Dravet Syndrome' OR 'DS, ' AND 'pharmacotherapy, ' AND 'treatments.' Randomized clinical trials, structured reviews, and meta-analyses were selected for in-human application of well-known anti-seizure medications; while in-vivo experiments on models of DS were selected to evaluate the potential of new therapeutic strategies. Expert opinion: The search for new pharmacological treatment options is led by the need for care and defeat of the natural course of the disease, an aspect still largely neglected by the available therapeutic strategies. Yet, the last 6 years have led to a climate of increased interest and availability of clinical trials. Particularly, gene therapy could hopefully prevent DS evolution by directly relieving the specific genetic defect, although the possibility of off-target editing, and the uneasy administration route have still largely prevented its use.